The use of essential oils as a growth promoter for small ruminants: a systematic review and meta-analysis [version 1; peer review: 2 approved] - Faizal Andri; Asri Nurul Huda; Marjuki Marjuki (F1000Research, 2020)
Background: Due to their antimicrobial properties and safety, essential oils are currently proposed as a sustainable option for antibiotic alternatives in the livestock sector. This current systematic review and meta-analysis investigated the effects of dietary essential oil supplements on growth response of small ruminants. Methods: A total of 12 studies (338 small ruminants) were included in this meta-analysis. The overall effect size was quantified using Hedges’ g with 95% confidence interval (CI) using a fixed-effect model. Publication bias was inspected using Begg’s and Egger’s tests, followed by trim and fill method to detect the number of potential missing studies. Results: Insignificant heterogeneity among studies was detected both on dry matter intake (DMI; P of Q = 0.810; I-square = 0.00%), average daily gain (ADG; P of Q = 0.286; I-square = 17.61%), and feed conversion ratio (FCR; P of Q = 0.650; I-square = 0.00%). The overall effect size showed that essential oils supplementation had no significant impact on DMI (Hedges’ g = -0.12; 95% CI = -0.50 to 0.26; P = 0.429) and FCR (Hedges’ g = -0.17; 95% CI = -0.55 to 0.22; P = 0.284), but had a significant positive impact on ADG (Hedges’ g = 0.44; 95% CI = 0.12 to 0.76; P = 0.002). The result of publication bias analysis showed that DMI, ADG, and FCR did not present any significant biases (P > 0.10), and no potential missing studies detected. Conclusions: Dietary essential oil could improve ADG of small ruminants, without any alteration on DMI and FCR. Further research in this topic is still required to provide stronger evidence of the potency of essential oil as a growth promoter for small ruminants.